2012
DOI: 10.21236/ada594451
|View full text |Cite
|
Sign up to set email alerts
|

Combining Low-Energy Electrical Resistance Heating with Biotic and Abiotic Reactions for Treatment of Chlorinated Solvent DNAPL Source Area

Abstract: REPORT DOCUMENTATION PAGEForm Public reporting burden for this collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing this collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden to Department of Defense, Washington Headquarters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…For design, practitioners can perform heat transfer calculations to identify regions of the subsurface susceptible to accelerated reaction kinetics, and couple the results to literature, laboratory‐derived, and/or field‐measured degradation rates. “Low‐temperature” ERH and TCH designs, on wider grid spacings, have also been used to accelerate EISB, zero‐valent iron (ZVI), and hydrolysis reactions without active extraction (e.g., Macbeth et al 2012; Singer 2014; Smith et al 2017). However, given the similar power delivery infrastructure and longer time frames necessary to evenly heat the subsurface on a wider grid spacing, the costs of heating all the way to boiling may be only incrementally higher.…”
Section: Technology Developmentsmentioning
confidence: 99%
“…For design, practitioners can perform heat transfer calculations to identify regions of the subsurface susceptible to accelerated reaction kinetics, and couple the results to literature, laboratory‐derived, and/or field‐measured degradation rates. “Low‐temperature” ERH and TCH designs, on wider grid spacings, have also been used to accelerate EISB, zero‐valent iron (ZVI), and hydrolysis reactions without active extraction (e.g., Macbeth et al 2012; Singer 2014; Smith et al 2017). However, given the similar power delivery infrastructure and longer time frames necessary to evenly heat the subsurface on a wider grid spacing, the costs of heating all the way to boiling may be only incrementally higher.…”
Section: Technology Developmentsmentioning
confidence: 99%
“…This modest increase in temperature can improve treatment system performance by both biotic and abiotic mechanisms. Primary dechlorinating bacteria (e.g., Dehalococcoides and Dehalogenimonas) are known to be mesophilic; hence, microbial activity and biodegradation can be significantly enhanced by increasing temperature to approximately 30-40 • C. Laboratory studies have demonstrated that the rate of dechlorination increased (at least) fourfold by increasing temperature from 10 to 30 • C (Macbeth et al 2012). Hydrolysis rates are highly temperature dependent for some compounds.…”
Section: Introductionmentioning
confidence: 99%
“…10,14 MRD is relatively inexpensive and effective for remediating contaminant plumes that may be economically infeasible to treat using more intensive methods. 16 Elevated subsurface temperatures during or following thermal treatment can directly stimulate the growth and activity of dechlorinating bacteria 10,17 or provide indirect benefits such as increasing the availability of electron donors. 5,7,18 Insufficient electron donor availability often limits MRD, especially in low permeability zones where traditional biostimulation techniques (e.g., substrate amendment) are difficult to implement.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Simultaneous or sequential implementation of remediation technologies may produce synergistic effects that reduce the cost and time required to achieve remedial objectives. For example, coupling of thermal treatment with microbial reductive dechlorination (MRD) shows promise as a combined remedy at sites impacted by tetrachloroethene (PCE), trichloroethene (TCE), and their chlorinated transformation products. , Both technologies are effective standalone methods for chlorinated solvent remediation, but complete contaminant mass removal with a single technology is rare. Thermal treatment technologies such as electrical resistance heating (ERH) are typically designed to increase subsurface temperatures to 80–110 °C, promoting rapid contaminant mass removal via desorption and volatilization; however, high levels of organic matter may hinder effectiveness due to stronger binding of contaminants to the solid phase, and high energy requirements preclude prolonged operation, making the technology best suited for source zone removal. , MRD is relatively inexpensive and effective for remediating contaminant plumes that may be economically infeasible to treat using more intensive methods . Elevated subsurface temperatures during or following thermal treatment can directly stimulate the growth and activity of dechlorinating bacteria , or provide indirect benefits such as increasing the availability of electron donors. ,, …”
Section: Introductionmentioning
confidence: 99%